Leaving the Nest or Living with Parents: Evidence from Mexico’s Young Adult Population - García Andrés, Adelaido; Martínez, José N.; Aguayo Téllez, Ernesto (Springer, 2021)
What makes adult children live with their parents? This paper examines the extent to which individual and family characteristics are associated with co-residence decisions between adult children and their parents. Using Mexico’s 2011 Social Mobility Survey (EMOVI) retrospective data and focusing on the young adult population in Mexico, we test empirically what parent and adult children characteristics correlate with co-residence status. Marginal effects from a probit regression model show that, after controlling for individual characteristics and retrospective family conditions, adult children’s education and employment status seem to be correlated with co-residence status, although only for males. Marital status, whether or not they have children, and retrospective parents’ home ownership are all correlated with co-residence status. The probability of adult male children staying at their parents’ home is reduced when the father has higher levels of education, while increased when the mother has higher levels of education.